Cytokine-Regulation of Na+-K+-Cl− Cotransporter 1 and Cystic Fibrosis Transmembrane Conductance Regulator—Potential Role in Pulmonary Inflammation and Edema Formation - Weidenfeld, Sarah; Kuebler, Wolfgang M. (Frontiers in Immunology, 2017)
Pulmonary edema, a major complication of lung injury and inflammation, is defined as accumulation of extravascular fluid in the lungs leading to impaired diffusion of respiratory gases. Lung fluid balance across the alveolar epithelial barrier protects the distal airspace from excess fluid accumulation and is mainly regulated by active sodium transport and Cl− absorption. Increased hydrostatic pressure as seen in cardiogenic edema or increased vascular permeability as present in inflammatory lung diseases such as the acute respiratory distress syndrome (ARDS) causes a reversal of transepithelial fluid transport resulting in the formation of pulmonary edema. The basolateral expressed Na+-K+-2Cl− cotransporter 1 (NKCC1) and the apical Cl− channel cystic fibrosis transmembrane conductance regulator (CFTR) are considered to be critically involved in the pathogenesis of pulmonary edema and have also been implicated in the inflammatory response in ARDS. Expression and function of both NKCC1 and CFTR can be modulated by released cytokines; however, the relevance of this modulation in the context of ARDS and pulmonary edema is so far unclear. Here, we review the existing literature on the regulation of NKCC1 and CFTR by cytokines, and—based on the known involvement of NKCC1 and CFTR in lung edema and inflammation—speculate on the role of cytokine-dependent NKCC1/CFTR regulation for the pathogenesis and potential treatment of pulmonary inflammation and edema formation.